2011
DOI: 10.3174/ajnr.a2426
|View full text |Cite
|
Sign up to set email alerts
|

Dampening of Blood-Flow Pulsatility along the Carotid Siphon: Does Form Follow Function?

Abstract: BACKGROUND AND PURPOSE:The tortuous distal part of the ICA may have an attenuating effect on pulsatile arterial flow. We investigated local arterial blood flow patterns in the ICA proximal and distal to the carotid siphon to detect quantitative waveform changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
39
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 32 publications
(33 reference statements)
4
39
0
1
Order By: Relevance
“…The elastic vessel wall can react on the applied force with a distension during systole and a retraction during diastole, laminarizing downstream pulsatile flow appropriate to a Windkessel reservoir. 18,28 The results of the present study are plausible because the acquired values are consistent with low intersubject variability. The acquired values of blood velocity, PI, and RI are in good accordance with Doppler sonography measurements reported in the literature.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The elastic vessel wall can react on the applied force with a distension during systole and a retraction during diastole, laminarizing downstream pulsatile flow appropriate to a Windkessel reservoir. 18,28 The results of the present study are plausible because the acquired values are consistent with low intersubject variability. The acquired values of blood velocity, PI, and RI are in good accordance with Doppler sonography measurements reported in the literature.…”
Section: Discussionsupporting
confidence: 76%
“…Here, a marked attenuation of blood flow pulsatility occurs along a short-but-curved vessel section with comparable uniformity to the Atlas slope, the carotid siphon. 18 During recent years, there has been increasing evidence about the negative impact of increased arterial flow pulsatility on the brain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies found that pulsatile flow is affected by physiological and pathological vascular geometry when investigating in a proximal-distal approach. 13,30,31 An important finding in this study was that the pulsatile flow that reaches distal arterial segments was augmented with age. Firstly, the PIs in large proximal arteries were increased in elderly (Table 2) and secondly the dampening capacity of the cerebral arteries was more efficient in the young group for all cerebral arterial segments (Table 3).…”
Section: Dampening Of Pulsatile Flow In the Cerebral Arteriesmentioning
confidence: 70%
“…6 Previous studies have suggested a relationship between increased middle cerebral artery (MCA) pulsatility measured by transcranial Doppler ultrasound and leukoaraiosis or lacunar infarction in patients with hypertension 7 and diabetes, 8 although not necessarily independent of age. However, increased cerebral pulsatility has often been interpreted as a consequence of small vessel disease due to changes in downstream resistance 9 rather than as a causal factor related to increased central arterial stiffness and reduced damping of the cerebral arterial waveform, 10 yet the cerebral circulation appears to be specifically adapted to dampen the arterial waveform 11 and increased aortic stiffness has been associated with leukoaraiosis, 12 lacunar stroke, 13 and cerebral pulsatility. 10 However, these relationships all strongly covary with age and are susceptible to residual confounding.…”
mentioning
confidence: 99%